Desistance and correctional interventions: a comparative analysis of theoretical approaches and practical outcomes in criminal justice systems - Mihăilă, Maria-Marinela (Technium Social Sciences Journal, 2025)
The concept of desistance from crime has gained increasing attention as a critical framework for understanding long-term behavioral change among offenders. This article offers a comparative analysis of desistance-oriented correctional interventions across different criminal justice systems, with a focus on how theoretical paradigms—such as cognitive-behavioral, narrative identity, and restorative justice approaches—influence practical rehabilitation outcomes. Drawing on empirical studies and policy evaluations, the paper contrasts intervention models implemented in both punitive and rehabilitative contexts, including those in Northern and Western Europe, North America, and emerging programs in Eastern Europe. The analysis emphasizes the role of psychosocial factors, institutional culture, and post-release support mechanisms in fostering sustained desistance. Findings suggest that interventions aligned with the principles of procedural justice, individualized support, and identity reconstruction are more effective in promoting long-term disengagement from criminal behavior. The article concludes with implications for policy development and the design of correctional programs, highlighting the need for culturally responsive and evidence-based practices that support the complex pathways toward desistance.